KAJIAN PRIORITAS SNI BIDANG PERIKANAN YANG PERLU DIKEMBANGKAN DALAM RANGKA INTEGRASI EKONOMI ASEAN - Ellia Kristiningrum (Badan Standardisasi Nasional, 2006)
Economic Integration has specified 11 sectors of priority of ASEAN and required these sectors to be integrated, one of them is fisheries product sector. ASEAN integration has obliged each member of ASEAN to develop programs of priority of product standard that need to be harmonized, including fisheries product. This study analyzed SNI of fisheries product that should be reviewed in order to improve the development of fisheries product standard. Result of this study is the priority for the development of SNI of fisheries product standard, determined base on the biggest value of export, import and the ASEAN agreement of harmonization for fisheries standard which are safety and quality management system, fish and fisheries sanitary measurement, testing and procedure for quarantine, quality standard and using of chemical raw.